Changes in periurethral microflora after antimicrobial drugs. Issue 6 (June 1991) - Lidefelt, K J; Bollgren, I; Nord, C E
Abstract : The periurethral flora was examined in 18 girls by use of a quantitative sampling method before, during, and three weeks after treatment with antibiotics for upper respiratory tract infections. Eight girls received amoxicillin. In five of them the anaerobic flora showed a reduction in total counts and in numbers of different species, and all eight girls got a heavy colonisation with enterobacteria during treatment. Three weeks after treatment the anaerobic and aerobic flora had reversed to the pretreatment composition. In 10 girls treated with trimethoprim-sulphamethoxazole the anaerobic flora remained unaffected and no enterobacterial overgrowth was registered during the study period. We propose that antibiotics could be one among several factors involved in the pathogenesis of urinary tract infection, by suppression of the anaerobic microflora and promotion of the colonisation with enterobacteria.